2021
DOI: 10.3390/children8070535
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multidisciplinary Aerodigestive Program: An Institutional Experience

Abstract: We share our experience on the implementation of a multidisciplinary aerodigestive program comprising an aerodigestive team (ADT) so as to evaluate its feasibility. We performed a retrospective chart review of the patients discussed at the monthly ADT meetings and analyzed the data. A total of 98 children were referred to the ADT during the study period. The number of cases increased steadily from 3.5 cases per month in 2019 to 8.5 cases per month in 2020. The median age of patients was 34.5 months, and 55% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Aerodigestive programs, for example, have grown in prevalence across the United States and internationally. 21,22 Although aerodigestive programs vary in their individual structure, they are generally meant to provide comprehensive and cohesive care to infants and children with complex congenital or acquired respiratory, feeding, neurologic, and gastrointestinal conditions. 1 The patient demographics reported in this survey emphasizes the ongoing medical complexity being managed by pediatric aerodigestive providers (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerodigestive programs, for example, have grown in prevalence across the United States and internationally. 21,22 Although aerodigestive programs vary in their individual structure, they are generally meant to provide comprehensive and cohesive care to infants and children with complex congenital or acquired respiratory, feeding, neurologic, and gastrointestinal conditions. 1 The patient demographics reported in this survey emphasizes the ongoing medical complexity being managed by pediatric aerodigestive providers (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary care models have gained popularity in a variety of fields within pediatrics from weight management clinics, oncology clinics, to gender‐affirming care clinics, and have been developed to integrate multiple different types of providers, specialists, and services within one centralized clinic for patients, thereby reducing care coordination burdens for patients and families. Aerodigestive programs, for example, have grown in prevalence across the United States and internationally 21,22 . Although aerodigestive programs vary in their individual structure, they are generally meant to provide comprehensive and cohesive care to infants and children with complex congenital or acquired respiratory, feeding, neurologic, and gastrointestinal conditions 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Aerodigestive patients present multiple comorbidities and can present a high prevalence of neurological impairment as showed in present study group (56%) and is also reported by Kim et al in 85% of patients. 19 Neurologically impaired children should undergo both clinical and instrumental dysphagia assessments since clinical swallowing assessments are not sensitive enough to diagnose aspiration consistently, especially in high-risk populations. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Upper GI evaluation may include video fluoroscopic evaluation of swallowing, contrast imaging for esophageal strictures, impedance pH testing for gastroesophageal reflux disease (GERD), esophageal manometry for motility disorders and mucosal endoscopic assessment for esophagitis including eosinophilic esophagitis (EoE). Aerodigestive patients often have feeding problems and are at high risk for malnutrition, necessitating feeding tube placement and use[ 11 ]. Some patients can be managed with nasogastric and gastrostomy tubes while others require jejunal feeds due to persistent GERD and/or intolerance to intragastric feeds.…”
Section: Aerodigestive Program Servicesmentioning
confidence: 99%
“…Frequency of unnecessary evaluation (swallow studies and impedance pH testing) dropped when such programs were established[ 24 , 25 ]. Aerodigestive programs have been linked to improved patient quality of life and reduced caregiver burden[ 11 ]. Studies have also noted shortened time to diagnosis (6 d vs 150 d, P < 0.001), fewer specialist consultations, lower hospital charges, less radiation exposure and reduced anesthesia exposure when aerodigestive programs were established[ 4 , 26 ].…”
Section: Aerodigestive Program Outcomesmentioning
confidence: 99%